MOTIVASI DAN KEPATUHAN MINUM OBAT ANTI TUBERKULOSIS - Jumiati, Nyemas; Wahyuni, Tri; Rahmawati, Annisa (Literasi Intelektual, 2024)
Background: Pulmonary tuberculosis (TB) is an infectious disease and a major cause of poor public health in many countries. It remains the leading infectious killer worldwide, with approximately 10 million people affected in 2018. The treatment of pulmonary TB generally lasts for six to nine months and consists of two phases—an initial intensive phase and a continuation phase. Interviews with 10 TB patients revealed that some experienced the desire to discontinue treatment due to a lack of self-motivation to recover. Efforts to control the high prevalence of pulmonary TB must focus on improving patient adherence to anti-tuberculosis therapy. Objective: To determine the relationship between motivation and adherence to anti-tuberculosis medication among TB patients attending the DOTS Clinic at Dr. Soedarso General Hospital, Pontianak. Methods: This study employed a cross-sectional design using a purposive sampling technique. The total sample consisted of 45 respondents. Results: Most respondents were aged 17–25 years (44.4%), female (46.7%), had completed senior high school (44.4%), were unemployed (57.8%), and had a TB history of ≥5 years (91.1%). More than half of the respondents demonstrated good motivation toward anti-tuberculosis medication (53.3%), and the majority were adherent to their treatment (84.4%). Conclusion: There is a significant relationship between patient motivation and adherence to anti-tuberculosis medication.